Macs for dummies - Baig, Edward C. (--For dummies., 2011)
The fun and easy way to make the most of your wonderful Mac Simply Mac-nificent - all the cool things your Mac can do! This handy guide helps you figure out the nuts and bolts of your Mac. Navigate the Mac desktop, use the Safari Web browser to surf the Internet, e-mail photos to friends and family, create and print documents, rip audio CDs, and more. The fun begins right here! Open the book and find:How to set up and configure your MacTips for getting around on the Mac desktopSteps for setting up an e-mail account and browsing the InternetDetails about the free.